Pengaruh Financial Literacy, Financial Attitude Dan Pendapatan Terhadap Perilaku Pengelolaan Keuangan Pada Pelaku Umkm Fashion Di Kota Batu - Inayati Widya Sari; Jeni Susyanti; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The purpose of this research is determine simultaneously and partially between the influence of financial literacy, financial attitude and income towards financial management behavior on MSME fashion actors in city Batu. The population used in this study is MSME fashion practitioners in city Batu, totaling 468 business actors while The sampling technique uses purposive sampling method with predetermined criteria of 50 business actors, with the sampling technique by distributing questionnaires. This type of research is explanatory research using a quantitative approach. Data analysis using multiple linear regression, test instruments, classic assumption tests, simultaneous tests (F test), partial tests (t test) and hypothesis testing using the SPSS program. The results showed that there was simultaneously an influence between financial literacy variables, financial attitudes and income towards financial management behavior. Whereas partial shows financial literacy (X1) and income (X3) influences financial management behavior (Y), while financial attitude (X2) does not affect financial management behavior